Relationship between impact energy and compression toughness energy of high-strength fiber-reinforced concrete - Marar, Khaled; Eren, Özgür; Çelik, Tahir (Elsevier B.V, 2001)
A simple, economical, and practical drop-weight impact testing machine was developed to determine the impact resistance for high-strength fiber-reinforced concrete (HSFRC) composite. Impact and compression tests were carried out on concrete cylinders reinforced with three different aspect ratios of hooked-end steel fibers l/d (length/diameter): 60, 75, and 83 (30/0.50, 60/0.80, and 50/0.60 mm/mm), and four different percentages of steel fibers 0.5%, 1.0%, 1.5% and 2.0% by volume of concrete. For each aspect ratio and volume of fibers, complete stress-strain curves of HSFRC were generated in order to determine the total energy absorbed for each cylindrical specimen in compression. The addition of steel fibres to concrete has improved impact resistance and also the compression toughness. The test results showed that a logarithmic relation exists between compression toughness energy (E ) by means of the generated stress-stress curves from the compressive tests and the impact energy (E ) by means of the modified impact machine for HSFRC at different l/d ratio of 60, 75, and 83
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Impact energy, Compression toughness energy; High-strength fiber-reinforced concrete, Stress–strain curve; stress-strain curve, compressive strength, impact energy